HIBURAN WALIMATUL URSY MENURUT PEGAWAI KANTOR URUSAN AGAMA (KUA) BALIKPAPAN TIMUR - Azhar, Muh. Zaim; Hamka, Hamka (Moderation | Journal of Islamic Studies Review, 2024)
Entertainment in a wedding party is a normal activity to do, since the time of the Prophet's entertainment when the Walimatul Ursy event was also held, the problem is if the entertainment that indulges the genitals and brings lust so that even though no longer sacred. This study aims to explore the perception of KUA Balikpapan east employees of the phenomenon that occurs in the community about entertainment during weddings. The method in this research is field research, which is qualitative in nature with a sociological approach, to collect data, researchers use techniques through interviews, observations and documentation and go directly to the field to get information from respondents needed. The conclusion in this study is that East Balikpapan KUA employees allow entertainment in the event Walimatul Ursy but they disagree with entertainment accompanied by music, some agree, and some are not necessarily they have a basis for what he chose.